نحو نظام مخطّط عقاري رقمي يعبّر عن الواقع - زوباري, علي عز الدّين (Latakia University Journal -Engineering Sciences Series, 2014)
إنّ الهدف الرئيس لهذا البحث هو تصميم نظام لمخطّط عقاري رقمي يعبّر عن الواقع الفعلي، ويكون شاملاً لأنواع البيانات المتعلقة بالعقارات (البيانات العقارية والتنظيمية والمعمارية والخدمية)، ويسمح بالحصول على كافة البيانات المتعلقة بالعقارات الأم والعقارات المفرزة أفقياً، وبيانات الأبنية والشقق الناتجة عن الإفراز الطّابقي، والشوارع بأنواعها، والمناطق العمرانيّة وخصائصها وفق نظام ضابطة البناء، فيكون مصدراً أساسياً للمعلومات من أجل تنفيذ التعاملات العقارية والتخطيط للمشاريع التنظيميّة والخدميّة. ولتحقيق هذا الهدف، تم تحديد البيانات اللازمة (المكانية والوصفية)، والحصول عليها من مصادرها المختلفة (الجهات التي تملك هذه البيانات) نسبة إلى المنطقة العقارية المدروسة، وبعد ذلك وباستخدام البرامج العلمية الحديثة المتوفرة والمتخصصة بالتعامل مع البيانات المكانية، تمت عمليات تنقيح البيانات وتنظيمها في ملفات، ثم بناء طبقات البيانات المكانية وجداول البيانات الوصفية وربط بعضها ببعض في بيئة نظم المعلومات المكانية. ولجعل بيانات نظام المخطّط العقاري المصمم تعبر عن الواقع الفعلي، فقد تم تطوير تصميم حديث لتمثيل البيانات؛ فالبيانات (المخطّطات والمواصفات) التي تظهر للمستخدم هي فقط تلك المنفذة على أرض الواقع وموجودة حالياً، وهذا يمكن تحقيقه تطبيق تحليلات واستعلامات مكانية على البيانات (المكانية والنصية) بواسطة البرمجيات العلمية التخصصية المستخدمة. ولجعل نظام المخطّط المصمّم أكثر فعالية في التخطيط والدراسة للمشاريع العقارية والتنظيمية والخدمية تم تأمين ربط العناصر المكانية في طبقات المخطّط (كالأبنية) مع ملفات معلومات خارجية، بحيث يمكن للمصممين و/أو المستخدمين وضع المعلومات اللازمة (مثل صور، نصوص، أرقام ...) فيها حسب الطلب. This research aims at developing an up-to-date digital cadastral plan system. This plan system is designed to be up-to-date, and to include all types of spatial and attribute data that related to parcels; such as cadastral data, regulation data, architectural data, and utilities data. So that, it designed and developed to be the main source of information for achieving the cadastral processes, and planning regulation, infrastructure and utilities projects. In order to perform this research aim, the needed data types were determined and obtained from different sources (authorities) related to the study area, then, by using the available modern scientific software -which specialized for treating and managing spatial data- the data were refined, regulated and stored into a specified files. After that, the spatial data layers and attribute tables were created, and the relationships between them also built in spatial information system environment. In order to make the plan system up-to-date, a new design was developed for data representation; this means that the presented data in the developed plan system must be exactly as the reality on the ground. This can be achieved by using the ability of the chosen scientific software, by achieving many types of analysis and queries on spatial data. In order to make the developed cadastral plan system effective and powerful, the ability of linking the features of the data layers (such as buildings) with exterior information files was available, so the designer and/or the user can input any needed information into these files (such as photos, text, numbers, … ).